Práticas avaliativas no ensino superior: um estudo com licenciaturas - Siqueira, Maria Terezinha Marques (2001)
The objective of this study is to reflect about the practice of leaming evaluation developed by teaching staff in the degree’s course. The research’s universe was formed per total of39 (thirty- nine) teachings that work with fínishing students of UNIPAR degree’s courses- Centre- Umuarama, in second semester in 2000 (two thousand), in spíte of this exercise their functions in one or more courses. Take part of the research’s sample, as subjects, 12 (twelve) teachears of different areas of teaching, wich were selected considering those who work in the subjects of Methodology and Teaching’s Practice and sixty-fíve fínishing students on 2000. The struments utilized to collect data with the teachers, was a questionaire with objective and subjective questions, and to the students were utilized structured interview, carried out in small groups, separatelly per degree’s course. This process permited establish compare data on the set of teachear’s speech and studenfs speech. On the beginnings chapters was discussed the conceptions of leaming’s evaluation, with basis in the presupposes of authority and emancipated conceptions from evaluation. Was noticed that the practice of leaming evaluation from degree’s course researched, is focused on measure, classifícation and verification of studenfs performance. The exam’s identifícation and written tests point out to a conception of authority practice of evaluation. If s pointed as a improvement suggestion of the estimate’s practice on emancipatory conception of evaluation like a contínuos diagnostic of leaming th at, by the opposite of authority estimate, constitute in a dialectics moment from the process of move foward in the development of action and growth to studenfs authority from the degree’s courses of the researched University. On the attempt to real and effectives transformations, the evaluation practice offer in this research look for to overcame the power relationships centralized on teacher and institution, to win a democracy space of collective participation, where the organization and educational plannig were tum rounded to an emancipatory practice, directioned a global graduation’s students.